Antisipasi Tindak Pidana Pencucian Uang Berkaitan Dengan Profesi Notaris dan Pejabat Pembuat Akta Tanah (PPAT) - Elrika, Elrika; Djaja, Benny (UNES Law Review, 2024)
The mode of Money Laundering Crime (TPPU) that often occurs in Indonesia is by utilizing the role of Notary and PPAT in performing their duties. Notaries and Land Deed Officials ("PPAT") become co-suspects in criminal cases, because they are suspected of assisting in the implementation of money laundering crimes, or other criminal acts involving deeds made. The research method used in writing this article is normative juridical research with a research approach using statutory regulations and using a theoretical or conceptual approach. The results of the analysis of the Notary and PPAT in carrying out their duties to anticipate money laundering apply the principle of Recognizing Service Users, if the Notary or PPAT finds suspicious transactions, they can report it to the Financial Transaction Reporting and Analysis Center (PPATK). In addition, Notary and PPAT are not responsible for the criminal act of money laundering committed by the parties or their clients who use the services of Notary or PPAT who require their services based on their authority. The position of the Notary and PPAT in exercising their authority to make authentic deeds is only as a recorder that is poured into a deed that gives rise to legal acts and has perfect evidentiary power. Notaries and PPAT are only obliged to report to PPATK if there are indications of money laundering committed by the parties or their clients through their services as Notaries or PPAT.